Famous men of modern biology - Berger, Melvin 1927- . (New York Crowell, 1968)
Biographical portraits of fourteen biologists who, in the past 100 years, have pursued research in disease, genetics, and the origin of life: Louis Pasteur, Robert Koch, Paul Ehrlich, Frederick Grant Banting, Alexander Fleming, Charles Darwin, Gregor Johann Mendel, Thomas Hunt Morgan, Hermann J. Muller, Wendell M. Stanley, Jonas E. Salk, Melvin Calvin, and Francis H. C. Crick and James Dewey Watson.
Includes index.
Keywords: Biologists